Peran Motivasi Sebagai Moderating Variable Pada Pengaruh Peran Konflik, Ambiguitas, EI, Dan SI Terhadap Kinerja Auditor : The Role of Motivation as a Moderating Variable on the Effect of the Role of Conflict, Ambiguity, EI, and SI on Auditor Performance - Imelda Dian R; Muhammad Nasih (Universitas Muhammadiyah Sidoarjo, 2020)
This study aims to determine the role of motivation variables on the effects of Role Conflict, Role Ambiguity, Emotional Intelligence, and Spiritual Intelligence on Auditor Performance in Public Accountants. Data were collected through a questionnaire method to 46 respondents using simple random sampling technique. This study uses quantitative analysis which includes validity, reliability, and hypothesis testing through the R2 test, t-test, f-test, and moderation regression analysis (MRA) test. Data analysis techniques using multiple linear regression and moderate regression analysis (MRA) which serves to prove the research hypothesis. The results showed that role conflict and role ambiguity had no partial effect on auditor performance, whereas emotional and spiritual intelligence had a partial effect on auditor performance. Role conflict, role ambiguity, emotional intelligence, and spiritual intelligence simultaneously affect auditor performance. Motivation is not a moderating variable but a moderate predictor.